Effective NO and SO2 removal from fuel gas with H2O2 catalyzed by Fe3O4/Fe0/Fe3C encapsulated in multi-walled carbon nanotubes. Issue 4 (August 2021) - Yang, Siyuan; Xu, Dan; Yan, Wenjie; Xiong, Yuanquan
Abstract: Multi-walled carbon nanotubes (MWCNTs) have been used as catalysts or supports in many industrial applications. Therefore, we provide a low-cost and environmentally friendly route to synthesize MWCNTs from plastics and red mud (RM), which is beneficial to the disposal of waste-solid. This nano-materials (RM-CNTs) are used as novel catalysts for CGPO to remove SO2 and NO from flue gas. It was unexpected that RM-CNTs exhibit a different catalytic pathway from the RM catalyst (traditional Fenton-like reaction) result from the constrained nano-scale reaction in which Fe3 O4 /Fe 0 /Fe3 C nanoparticles were encapsulated in MWCNTs. Combined with various quenching experiments and characterization analysis, the catalytic mechanism of RM-CNTs was clarified: (1) the in-situ carbothermal reduction increased the activity of the catalysts (Fe2 O3 →Fe3 O4 →Fe 0 →Fe3 C); (2) Fe 0 and Fe3 O4 can form a metal-semiconductor interface with extremely low resistance which can accelerate electron transfer; (3) Fe3 C as heterogeneous Fenton catalyst was rarely reported. The experimental results indicated that the activity of Fe-C bond was closely related to the type of carbon substrate during the formation process; (4) MWCNTs encapsulated Fe3 O4 /Fe 0 /Fe3 C particles exhibited excellent catalytic activity, which was due to the existence of 1 O 2 . Graphical Abstract: ga1 Highlights: A novel catalytic gaseous peroxide oxidation (CGPO) catalyst synthesized by co-pyrolysis method using solid waste red mud (RM) and plastics as a precursor. It was discovered for the first time that 1 O 2 mediated gas-phase Fenton-like process catalyzed by Fe3 O4 @Fe 0 @Fe3 C nanoparticles encapsulated in multi-walled carbon nanotubes. Fe 0 and Fe3 O4 can form a low resistance metal-semiconductor interface, which can promote the conversion of Fe 3+ to Fe 2+ . The excellent catalytic activity of RM-CNTs depends on the type of carbon substrate and catalytic reaction inside MWCNTs.